Crystal quality enhancement of semi-polar (11 22) InGaN/GaN-based LED grown on M-Plane sapphire substrate via MOCVD / Omar Ayad Fadhil - Omar Ayad , Fadhil (2019)
Gallium nitride (GaN) thin films grown along c-plane (polar) direction are extensively employed for III-nitride based LEDs. However, the wurtzite crystal structure of LEDs grown along c-plane direction suffers from the spontaneous and piezoelectric field, resulting in quantum-confined stark effect (QCSE), which impairs the device efficiency towards longer wavelengths. The growth of semi-polar (11-22) epitaxial layer have attracted substantial interest as it circumvents this issue. In this study, the Taiyo Nippon Sanso SR-2000 horizontal metal-organic chemical vapor deposition (MOCVD) was employed to assist the semi-polar (11-22) growth on m-plane sapphire substrate. Two main phases were employed, namely the growth of semi-polar (11-22) unintentionally doped-gallium nitride (uid-GaN) and the LED structure. The former phase consists of nitridation process, aluminum nitride (AlN) nucleation layer, AlN/GaN multi-layer (ML), and the uid-GaN. The ammonia (NH3) flux for the growth of uid-GaN was varied from 0.7 to 8.3 standard liter per minute (slm). The NH3 flux of the AlN growth was varied from 1-2.3 slm to investigate its influence towards the crystal quality of the uid-GaN. The AlN/GaN ML was varied from 20-60 to observe the enhancement of the crystal quality and the surface morphology of the semi-polar (11-22) uid-GaN. The second phase of this work was the LED structure, including of the n-type GaN, the InGaN/GaN multi-quantum wells (MQW) and the p-type GaN. The disilane (Si2H6) flow rate for the growth of n-type semi-polar (11-22) GaN epitaxial layers was varied from 10 to 20 standard cubic centimeter per minute (sccm). The bicyclopentadienyl magnesium (Cp2Mg) flow rate for the growth of p-type GaN was varied from 20 to 40 sccm to measure hole mobility and concentrations. Lastly, the trimethylindium (TMI) flow rate was varied at yield triethylgallium, TEG:TMI ratio of 1:1, 1:2 and 1:3 for the growth of InGaN/GaN active region. The compressive stress/strain state of the as-grown uid-GaN was examined by Raman spectroscopy at room temperature. The crystal quality of the epitaxial layers was characterized by high resolution X-ray diffraction (HR-XRD), including phase analysis (PA), on- and off-axis x-ray rocking curve (XRC) and reciprocal space mapping (RSM), and transmission electron microscopy (TEM). The surface morphology analysis was investigated by atomic force microscopy (AFM) and field emission scanning electron microscopy (FESEM). The optical and the electrical properties were analyzed by room temperature photoluminescence spectroscopy (PL), Hall effect and electroluminescence spectrum (EL) analysis. The full-width at half-maximum (FWHM) of semi-polar (11-22) InGaN/GaN LED with the use of AlN/GaN ML template was found to be as low as 0.11° and 0.30° along [-1-123] and [1-100], respectively. The values of root mean square (RMS) surface roughness and the peak-to-valley were obtained as low as 6.30 and 40.24 nm, respectively. Consequently, the semi-polar (11-22) InGaN/GaN LED grown on the AlN/GaN template exhibited superior indium incorporation with